Komunikasi Pemasaran terhadap Minat Beli Konsumen - Fikriansyah, Fikriansyah; Christantyawati, Nevrettia (JOPPAS: Journal of Public Policy and Administration Silampari, 2024)
This study aims to prove that marketing communications conducted by PT. Pinang Mas Bersaudara can attract consumer purchasing interest. This study uses a quantitative approach with data collected through questionnaires from 25 consumers who have transacted with PT. Pinang Mas Bersaudara. The results of the study found that marketing communications have a significant influence on consumer purchasing interest. This finding provides a deep understanding of the importance of marketing communications strategies in shaping consumer purchasing interest. It includes guidance for PT—Pinang Mas Bersaudara in designing more effective marketing strategies. Keywords: Marketing Communications, Purchase Interest, AIDA Marketing